Specify or design connectors that are suitable for the application - Galvan, Glenn (Knovel, 2011)
As an airline passenger is waiting in the terminal for his flight, he decides to plug in his tablet to charge the battery. As soon as he connects the AC/DC adapter to the tablet he hears a snap and he sees an error message on the tablets screen communicating that there is a power failure. Upon inspection he discovers that the connector has jarred loose and thus his battery is not charging his tablet. These problems are not uncommon for some of the mobile products that are being sold in the market place. Seeing the individuals frustrations from meager designs can have a dampening effect in terms of revenue and a companys reputation. To overcome some of the quality issues in connectivity the design engineer needs to consider many characteristics of the connector.